(untitled) (Dhaka University Journal of Science, 2012)
The possible utilization of rice husk activated carbon as an adsorbent for the removal of methylene blue dye from aqueous solutions has been investigated. In this study, activated carbons, prepared from low-cost rice husk by sulfuric acid and zinc chloride activation, were used as the adsorbent for the removal of methylene blue, a basic dye, from aqueous solutions. Effects of various experimental parameters, such as adsorbent dosage and particle size, initial dye concentration, pH and flow rate were investigated in column process. The maximum uptakes of methylene blue by activated rice husk carbon at optimized conditions (particle sizes: 140 ?m; Flow rate: 1.4 mL/min; pH: 10.0; initial volume of methylene blue: 50 mL and initial concentration of methylene blue: 4.0 mg/L etc.) were found to 97.15%. The results indicate that activated carbon of rice husk could be employed as low-cost alternatives to commercial activated carbon in waste water treatment for the removal of basic dyes. This low cost and effective removal method may provide a promising solution for the removal of crystal violet dye from wastewater. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11491 Dhaka Univ. J. Sci. 60(2): 185-189, 2012 (July)